Flexible resources and experiences of racism among a multi-ethnic adolescent population in Aotearoa, New Zealand: an intersectional analysis of health and socioeconomic inequities using survey data. Issue 10358 (1st October 2022) - Simon-Kumar, Rachel; Lewycka, Sonia; Clark, Terryann C; Fleming, Theresa; Peiris-John, Roshini
Summary: Background: As societies become increasingly diverse, understanding the complex nature of racism for multiple ethnic, social, and economic identities of minority youth is required. Here we explore the experience of racism between and among privileged majority adolescent groups and targeted minority (Indigenous and ethnic) adolescents in New Zealand. Using the concept of structural and embodiment flexible resources, which act as risk and protective factors, we examine the social and health effects on minority youth. Methods: In this intersectional analysis, we use self-reported data from the Youth2000 survey series administered in 2001, 2007, 2012, and 2019 to large, representative samples of students from mainstream state and private schools in the Auckland, Tai Tokerau, and Waikato regions of New Zealand. Students were in school years 9–13 and mostly aged 13–17 years. Ethnic or migrant group, income level of country of origin, and migrant generation were used as measures of structural resources and perceived ethnicity as a measure of embodiment resource. Racism and its effects were measured as socioeconomic inequities (household, neighbourhood, and school-level deprivation); interpersonal discrimination (unfair treatment, bullying, and safety); and health inequities (forgone health care, symptoms of depression, and attempted suicide). We used generalised linear models to explore variations in economic, interpersonal, and health outcomes for Indigenous and migrant youth, adjusting for mediating effects of household deprivation and measures of flexible resources (migration generation, income level of country of origin, and perceived ethnicity). Findings: We collected data from a total of 20 410 adolescents from the four survey waves between 2001 and 2019. Participants had a median age of 15 years (IQR 14–16). Socioeconomic, interpersonal, and health inequities varied with access to flexible resources among Māori and racialised migrant youth. Māori and racialised migrants from low-income and middle-income countries in particular experienced high levels of socioeconomic inequities. Racialised migrant youth experienced persistent socioeconomic inequities extending over three generations, especially Pasifika migrant adolescents. Minorities perceived as White experienced less discrimination and had more advantages than visibly racialised groups. Regression models showed that embodiment resources, and to a lesser extent structural resources, mediated, but did not eliminate ethnic disparities in socioeconomic status and interpersonal discrimination; these resources did not strongly mediate ethnic disparities in health. Trend analyses indicate consistency in these patterns with ethnicity-based inequities persisting or increasing over time. Interpretation: Indigenous and ethnic minority experiences of racism are heterogeneous. Structural flexible resources (wealth) and, more substantially, embodiment flexible resources (perceived Whiteness) mitigate individual experiences of racism. In multi-ethnic western societies, anti-racist interventions and policies must address both structural deprivation and associated intergenerational mobility and colourism (ie, implicit and explicit bias against non-White youth). Funding: Health Research Council of New Zealand.